2010
DOI: 10.1002/elps.201000490
|View full text |Cite
|
Sign up to set email alerts
|

Trends in nonpolar polymer‐based monolithic columns for reversed‐phase capillary electrochromatography

Abstract: This review article is concerned with describing the various strategies that have been introduced for the preparation of nonpolar polymer-based monolithic columns for RP-CEC. First, the various traditional ways of generating the EOF that involved the introduction of fixed charges on the surface of the monoliths are reviewed. This is followed by a description of the development of neutral monoliths as the most promising monoliths for the separation of a wide range of neutral and charged species at a relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 68 publications
0
22
0
2
Order By: Relevance
“…A valuable alternative for the analysis of positional isomers with overlapping spectra is CE . Significant advances have been achieved for the analysis of PAHs and PAH derivatives by CE and CEC . Baseline resolution of OH‐PAH positional isomers has been reported via γ‐cyclodextrin‐modified MEKC and CZE .…”
Section: Introductionmentioning
confidence: 99%
“…A valuable alternative for the analysis of positional isomers with overlapping spectra is CE . Significant advances have been achieved for the analysis of PAHs and PAH derivatives by CE and CEC . Baseline resolution of OH‐PAH positional isomers has been reported via γ‐cyclodextrin‐modified MEKC and CZE .…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported neutral monoliths (void of fixed charges) to completely eliminate electrostatic interactions nuisance created between charged solutes and the otherwise surface attached charged moieties, an approach that was originally described by Okanda and El Rassi [9] and recently by Karenga and El Rassi [10]. Two different series of monolithic columns were prepared with C8, C12 and C16 surface bound chains using the same crosslinking monomer pentaerythritol triacrylate (PETA).…”
Section: Nonpolar Organic Monoliths For Rpc Separationsmentioning
confidence: 99%
“…[ 18 ] It has recently been demonstrated that polymeric monoliths with neutral surface can generate an electroosmotic fl ow (EOF) through the adsorption of buffer molecules, [ 19 ] thus allowing for an extension of electrochromatographic applications of non-polar polymer-based monolithic columns. [ 20 ] Indeed, this permits to overcome the diffi culty to achieve the copolymerization of highly hydrophobic monomers (e.g., styrene and/or divinyl benzene) with hydrophilic monomers (e.g., sulfonic acidcontaining styrenic monomers).…”
Section: Instrumentationmentioning
confidence: 99%
“…The characterization of PS-DVB monoliths is carried out at the different stages of the synthesis using a combination of experimental techniques, thus providing information on the chemical and porous structures. All experimental results evidence the sole role of the PCL oligomer as a porogen.have been applied for reversed-phase, [ 4 ] ion-exchange and normal-phase, [ 5 ] chiral, [ 6 ] and hydrophilic interaction liquid chromatography (HILIC) [ 7 ] electrochromatography allowing for the separation of a broad range of molecules such as peptides, [ 8 ] proteins, [ 9 ] enantiomers, and so on. [ 10 ] In most cases, the preparation of polymer-based monoliths relies on thermally or photochemically triggered freeradical copolymerization of monomers in the presence of a porogenic solvent.…”
mentioning
confidence: 99%